AZOLLA PINNATA AS PARTIAL PROTEIN REPLACEMENT ON GROWTH PERFORMANCE OF CROSSBRED PIGS (Indian Journal of Animal Production and Management, 2014)
An experiment was conducted for 120 days in grower phase and finisher phase using eighteen crossbred Large White Yorkshire pigs to evaluate the effect of feeding of sun dried Azolla as a protein replacement on growth performance of crossbred pigs. Eighteen pigs were divided into three groups of six animals each. First group (T1) was maintained on routine farm concentrate. Pigs belonging to T2 and T3 groups were fed with 10 and 20 per cent azolla incorporated test rations, respectively. The cumulative body weight gains, ADG during grower phase and during finisher phase showed no significant difference (P
Keywords: Azolla; growth performance; replacement; crossbred; Large White Yorkshire